İmanoğlu kazı buluntularına yansıyan İ. Ö. III.-I. bin yıllarda Anadolu-Suriye ve Mezopotamya ilişkileri - Uzunoğlu, Edibe
Abstracts; The Relations between Anatolia, Syria and Mesopotamia from Third to First Millennium B.C. that are Reflected at the Excavation Finds of İmamoğlu (Malatya)